“Higher up, further” approaching air transport in postcolonial Africa through the biographies of planes - (:unkn) unknown (My University, 2024)
The 1960s were a pivotal moment for global air transport: the confluence of the technological innovations of the jet age and the formal decolonisation of most African countries resulted in a new connectivity between Africa and the world, as global aerial mobility rapidly intensified. This paper focuses on the multifaceted role of the jet plane in this process. Jets as flag carriers were key objects in terms of national representation on foreign ground for the newly independent nations. They featured prominently as icons of postcolonial African modernity, were diplomatic tools in the Cold War context and were valuable business assets in a competitive global market. The biographies of the first African-owned jets, Air Afrique's DC-8s and Ethiopian Airlines’ Boeing 720Bs, were analysed for this paper. Following these biographies brings to the fore the social life of planes as a new and exciting research avenue for postcolonial aerial infrastructure and geographies.
Keywords: African Research